Effect of Hydrocolloids and Tapioca Starch on Physicochemical and Nutritional Characteristics of Mung Bean Protein-Based Patties - Ratnaningsih, Ratnaningsih; Songsermpong, Sirichai; Nguyen, Phung Tien (Indonesian Food Science and Technology Journal, 2025)
Hydrocolloids are essential ingredients to enhance the quality of plant-based meat analogs due to their affinity for binding water and gel formation. Developing plant-based meat analogs remains a challenge, as they still struggle to mimic the texture, juiciness, and structure of real meat. This research aimed to study the influence of hydrocolloids and tapioca starch application on the physicochemical, dietary fiber, cooking qualities, and sensory evaluation of plant-based burger patties. The experiment used four treatments of hydrocolloids (without hydrocolloid (WH), and xanthan gum (XG), guar gum (GG), and carboxymethyl cellulose (CMC) at 0.5% of the total weight), combined with tapioca starch (0% and 2%) application. The results showed that the hydrocolloid application significantly enhanced moisture, ash, protein, carbohydrate, dietary fiber, lightness, yellowness, and hardness. At the same time, tapioca starch increases carbohydrates, calories, dietary fiber, hardness, and springiness. Tapioca starch decreased the cooking loss and water retention but increased cooking yield. A combination of 0.5% XG or 0.5% GG with 2% tapioca starch application showed no significant differences in appearance, flavor, or overall acceptability compared with commercial products, which are potentially developed for commercial use.